2007
DOI: 10.1111/j.1467-629x.2007.00225.x
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of activity management practices in public sector organizations

Abstract: This paper examines the extent to which activity management practices are adopted by Australian public sector organizations at each of Gosselin's (1997) levels of Activity Analysis, Activity Cost Analysis, and Activity-based Costing. The present paper replicates Baird "et al". (2004), thereby enabling a comparison of the extent of adoption of activity management in the public sector with that reported in the private sector in Baird "et al". (2004). The results reveal that the adoption of higher level activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
43
1
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 24 publications
3
43
1
5
Order By: Relevance
“…Bjørnenak, 1997;Gosselin, 1997;Krumwiede, 1998;Clarke et al, 1999;Groot, 1999;Malmi, 1999;Hoque, 2000;Baird et al, 2004;Brown et al, 2004;Al-Omiri and Drury, 2007;Baird, 2007). This paper extends this research to consider the factors that influence the inclusion of non-manufacturing overhead costs in product costs used in decision-making.…”
Section: Literature Reviewmentioning
confidence: 81%
“…Bjørnenak, 1997;Gosselin, 1997;Krumwiede, 1998;Clarke et al, 1999;Groot, 1999;Malmi, 1999;Hoque, 2000;Baird et al, 2004;Brown et al, 2004;Al-Omiri and Drury, 2007;Baird, 2007). This paper extends this research to consider the factors that influence the inclusion of non-manufacturing overhead costs in product costs used in decision-making.…”
Section: Literature Reviewmentioning
confidence: 81%
“…Notable approaches include the use of performance contracts. Similarly, activity based management practices can increase transparency and efficiency when conducting government activities thereby assisting public sector organizations to achieve their objectives (Baird, 2007;Melese et al, 2004). Historically, some public sector enterprises were formed to create employment for large numbers of people.…”
mentioning
confidence: 99%
“…could influence the diffusion of innovations in organizations (Adam & Fred, 2008;Al-Omiri & Drury, 2007a;Askarany, 2006;Askarany & Smith, 2004Berling, 2008;Englund & Gerdin, 2008;Qian & Ben-Arieh, 2008;Yazdifar, Askarany, Askary, & Daneshfar, 2005). However, while the majority of studies initiated by the above theories and metaphors and found some associations between management accounting changes and some contextual factors (addressed by adopted theories), the findings are inconclusive, inconsistent, and mixed (Al-Omiri & Drury, 2007a;Baird, 2007;Baird, Harrison, & Reeve, 2007;Cobb, Innes, & Mitchell, 1993;Innes & Mitchell, 1995;Innes, Mitchell, & Sinclair, 2000;Langfield-Smith, 1997;Pierce, 2004;. Furthermore, from organizations' point of views, understanding factors contributing to innovative behavior in organizations and influencing organizations' decisions to proceed with the changes have remained relatively undeveloped, inconclusive, and inconsistent (Cho & Pucik, 2005).…”
Section: Introductionmentioning
confidence: 95%
“…Recent studies suggest that the take-up of most of management accounting changes introduced during the past three decades still lag behind those of traditional systems (Al-Omiri & Drury, 2007b;Anderson & Young, 1999;Askarany, 2003;Askarany, Smith, & Yazdifar, 2007aAskarany & Yazdifar, 2007;Askarany, Yazdifar, & Askary, 2010;Baird, 2007;Gosselin, 1997;Langfield-Smith, 1997). For example, Chenhall and Langfield-Smith (1998) have found that the level of adoption of most of relatively new management accounting techniques in Australia were fairly lower than those of the traditional techniques.…”
Section: Literature Reviewmentioning
confidence: 99%